2019
DOI: 10.1016/j.heliyon.2019.e02753
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prognostic significance of MUC4β in mucoepidermoid carcinoma of the salivary glands: An immunohistochemical study

Abstract: Objectives– Routine histopathological grading for salivary gland mucoepidermoid carcinoma (MEC) have failed to prognosticate these tumors, resulting in poor post-surgical outcomes. In developing countries, the lack of technologically advanced infrastructure curtails, efficient treatment modalities. This study aimed at determining if MUC4β can characterize salivary gland MEC and serve as a practical and inexpensive method to prognosticate salivary gland MEC.Materials and methods– Fifteen cases of archived paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Moreover, mucoepidermoid carcinoma has no stromal secretions characterizing the tumors with myoepithelial differentiation, which are an important evidence of myoepithelial cells involvement and its differential diagnosis [22]. Although our sample size is limited and includes only ten cases of (MEC), this tumor is very rare and our sample size consistent with others [23], [24], [25].…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, mucoepidermoid carcinoma has no stromal secretions characterizing the tumors with myoepithelial differentiation, which are an important evidence of myoepithelial cells involvement and its differential diagnosis [22]. Although our sample size is limited and includes only ten cases of (MEC), this tumor is very rare and our sample size consistent with others [23], [24], [25].…”
Section: Discussionsupporting
confidence: 73%
“…Another study by Elsayed et al, (23) revealed MUC4 over expression in lung adenocarcinoma associated with aggressive behavior. According to (24) the reason for such inconsistent results in MUC4 correlations with many variables is that MUC4 might be a mediator or indication of tumor growth aggressiveness. MUC4 binds to ErbB2 and phosphorylates it on its tyrosine residues.…”
Section: Immunohistochemical Resultsmentioning
confidence: 99%
“…[135] There are few examples, such as mucoepidermoid carcinomas of the salivary gland, where overexpression correlates with a better prognosis. [136,137] However, in most scenarios, overexpression correlates with poor clinical outcomes, and MUC 4 expression level can be used as a prognostic marker. [11,138] So far, MUC4 was better explored as a therapeutic target for pancreatic cancer (PC).…”
Section: The Mucin Muc4mentioning
confidence: 99%